Differential Associations between Paraphilic Interests and Sexual Satisfaction. Issue 3 (31st March 2021) - Vander Molen, Lauryn; Ronis, Scott T.; Benoit, Aryn A.; Walmark, Sofia
Abstract: Although paraphilias encompass a broad range of sexual interests, they often are regarded broadly as maladaptive. Doing so, however, may conceal relatively well-adjusted and satisfying forms of sexuality. Participants were recruited through Amazon Mechanical Turk and completed online questionnaires assessing paraphilic interests, sexual satisfaction, resilience, and attachment. Participants were 614 adults, aged 19 to 30 years ( M  = 26.08, SD  = 3.18). Regression analyses demonstrated that atypical paraphilias, paraphilias related to nonconsensual sexual activities, and paraphilias related to BDSM explained a significant proportion of variance in sexual satisfaction. Findings suggest directions on the conceptualization and treatment of paraphilias.